Inovação frugal para potencializar a inovação nas micro e pequenas empresas em tempos de crise: caso pandemia COVID-19 - Cândido, Jéssica Morais (Universidade do Vale do Rio dos Sinos, 2020)
In the Brazilian context, perceive the lack of studies that comprehend the difficulties of micro and small companies in times of crisis and accessing the possibility to access the frugal innovation as base increase of organization of business in this context. Therefore, the present paper comprehends the principal difficulties of create new business in the micros and small companies cause for economic-sanitary crisis in 2020, based on this result, suggest the possibility of using frugal innovation as an alternative to generating of business in micro and small companies in this moment of crisis. The paper was based on a bibliographic research, using date from the Brazilian Service of Support to Micro and Small Businesses (SEBRAE) and a survey in the EBSCO database. Can be identified, from the relation difficulty and generation of new business, greater emphasis on the management processes of difficult micro and small companies, innovation is considered a strategic issue, but it is used in a restricted way in practice and in a limited way when considering frugal innovation. Based on bibliographic surveys, a theoretical model is elaborated, using frugal innovation as a basis for generating new business in times of crisis. In the composition of the model, several tools are used as a method for generating new business in micros and small companies, taking into account their difficulties in times of crisis.
Keywords: Micro e pequenas empesas; Dificuldades; Crise; Inovação Frugal; Micro and small companies; Difficulties; Crisis; Frugal Innovation